2018
DOI: 10.15560/14.6.1109
|View full text |Cite
|
Sign up to set email alerts
|

First report of Psammolestes tertius Lent & Jurberg, 1965 (Hemiptera, Reduviidae, Triatominae) in Rio Grande do Norte state, Brazil

Abstract: We report the first known occurrence of Psammolestes tertius Lent & Jurberg, 1965 (Hemiptera, Reduviidae, Triatominae) in the state of Rio Grande do Norte, Brazil. In 2009 and 2017, 2 adult specimens, a female and a male respectively, were collected at the Seridó Ecological Station, which is located in the municipality of Serra Negra do Norte. These records broadens the geographical distribution of P. tertius in Brazil and the biodiversity of triatomines in Rio Grande do Norte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Consequently, it was possible to include a large number of research voucher specimens: whole/semi-whole triatomine specimens, triatomine body parts (e.g., wings, genitalia, heads, legs, and abdomens), and/or DNA samples. The storage of these triatomine body parts and of DNA samples in the collection allows access to biological material used in diverse research areas, such as taxonomic and ecological studies (e.g., Ferreira et al 2014;Silva et al 2018;Rengifo-Correa et al 2020;Gurgel-Gonçalves et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it was possible to include a large number of research voucher specimens: whole/semi-whole triatomine specimens, triatomine body parts (e.g., wings, genitalia, heads, legs, and abdomens), and/or DNA samples. The storage of these triatomine body parts and of DNA samples in the collection allows access to biological material used in diverse research areas, such as taxonomic and ecological studies (e.g., Ferreira et al 2014;Silva et al 2018;Rengifo-Correa et al 2020;Gurgel-Gonçalves et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of P. lenti in Tocantins, which opens the possibility of research about the ecology, distribution, and epidemiological importance of this species in this state. Similarly, the research voucher specimens relating to the first report of Psammolestes tertius Lent & Jurberg in the state of Rio Grande do Norte (Silva et al 2018) are deposited in the collection. Together, these deposited specimens underscore the importance of the collection for entomological surveillance, research, and preservation of recently reported specimens collected beyond their known distribution limits.…”
Section: Discussionmentioning
confidence: 99%
“…Psammolestes spp. are endemic species in South America; P. arthuri was reported in Colombia and Venezuela [ 12 ], P. coreodes was reported in Argentina, Bolivia, Brazil and Paraguay [ 12 , 13 ], and P. tertius was reported in Brazil and Peru [ 12 , 14 , 15 ]. The close association of these species with birds suggests that these vertebrates are the main source of food for these triatomines in the wild [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The close association of these species with birds suggests that these vertebrates are the main source of food for these triatomines in the wild [ 16 ]. These vectors have already been found in bird nests of the families Dendrocolaptidae, Troglodytidae, Furnariidae and Icteridae [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%